ANALYSIS OF FACTORS AFFECTING THE USE OF CERTIFIED CATFISH BREEDERS ON CATFISH SHUTERS IN TEGAL DISTRICT - Wijanarko, Yusuf; Santoso, Imam; Priyono, Slamet (Jurnal Media Akuakultur Indonesia, 2022)
There are still catfish hatcheries found in Tegal District that use brooders derived from the results of rearing spread seeds (jonggolan), not catfish specifically for certified breeders. The use of jonggolan as broodstock is feared to cause a decrease in the quality of catfish fry due to inbreeding or inbreeding. This research is expected to be able to determine the factors that influence the use of certified catfish broodstock so that prevention can be done to avoid losses to catfish farmers and improve the steps that need to be decided in making policies at the relevant agencies.This study uses a descriptive correlational statistical analysis method. The data was taken from all catfish hatcheries in Tegal District with a total of 100 respondents then the data was processed with SPSS 24 year 2022 software.The variables of age, last education, training or socialization about fisheries that have been followed, and the origin of the broodstock used have a significance value greater than 0.05. then there is no significant correlation (relationship) to the parental strain variable used. The Capital Estimation variable has a significance value less than 0.05 (Sig. 0.000). then there is a significant correlation (relationship) to the parental strain variable used. Spearman correlation value of 0.351 indicates that the direction of the correlation is positive with a weak correlation strength.Age factor, last education, training or socialization by the Fisheries Service that has been followed, the origin of the broodstock (government assistance, independent purchase or jonggolan) does not affect the use of certified catfish breeders. Capital owned factors that influence the decision of farmers in using certified catfish broodstock.